2009
DOI: 10.1089/lrb.2009.0008
|View full text |Cite
|
Sign up to set email alerts
|

Local Tissue Water in At-Risk and Contralateral Forearms of Women with and without Breast Cancer Treatment-Related Lymphedema

Abstract: Background: Quantitative measurements to help detect incipient or latent lymphedema

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…It has previously been proposed that a TDC threshold of 1.26, based on three standard deviations above the mean measures of 60 women without BCRL, 14 be used for the inter-arm ratio of TDC affected arm TDC unaffected arm to differentiate women with and without lymphedema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been proposed that a TDC threshold of 1.26, based on three standard deviations above the mean measures of 60 women without BCRL, 14 be used for the inter-arm ratio of TDC affected arm TDC unaffected arm to differentiate women with and without lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…The 1.26 TDC threshold was based on measures using the medium probe with a penetration depth of 2.5 mm. 14 TDC values are depth dependent 24,30 and although the use of inter-arm ratios may have reduced the effect of variation with measurement depth, this threshold may not be applicable for measures made with the extra-small and small probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TDC technique in the assessment of lymphedema has been described in the literature. 19,[27][28][29][30][31][32][33][34] The device, (MoistureMeterD, Delfin Technologies Ltd, Finland), consists of four open-ended coaxial probes intended to measure tissue water at effective depths from 0.5 to 5 mm. The dimensions of the coaxial probes define the penetration of EM fields in tissue.…”
Section: Measurement Systemsmentioning
confidence: 99%
“…14,16,18 Therefore, measurements of tissue water are best focused into skin where the first signs of lymphedema are often thought to manifest [19][20][21][22][23][24] and where edema is often located. 25,26 Using this approach, Mayrovitz 27-28 and Mayrovitz et al [29][30][31][32][33][34] found in lymphedema patients significantly greater ratios of affected to contralateral arm TDC values than ratios of arm volumes or girths.…”
Section: Introductionmentioning
confidence: 99%